Forest use and management of woody vegetation in the fundo legal of Yaxcabá, Yucatan, Mexico - Rodríguez-Sánchez, Perla Victoria; Levy-Tacher, Samuel Israel; Ramírez-Marcial, Neptalí; Estrada-Lugo, Erin Ingrid Jane (Instituto de Ecología, A.C., 2020)
Background and Aims: The fundo legal (FL) is a strip of forest vegetation that peripherally delimits the villages, provides multiple ecosystem servicesand is part of the mayan community forest reserves of the Yucatan Peninsula. The objective of this study was to describe the forms of use and managementof FL woody vegetation by the inhabitants of the community of Yaxcabá, Yucatan, Mexico.Methods: Within the FL, three sections were selected based on the number of roads identified. Eight sampling plots of 400 m2 (20 × 20 m) and eightmore plots of mature vegetation (MV) were established in each section. In each plot the diameter of the stumps was measured and their taxonomicidentity was determined. The richness, diversity, density and basal area of the stumps and each section was contrasted with sampling plots with MVoutside the FL and with little evidence of use. A closed survey was applied to the local people to detail the forms of local use and management thatresidents carry out in the FL.Key results: There were 58 useful species that included 42 genera and 22 families of angiosperms, of which Fabaceae, Polygonaceae and Ebenaceaewere the most abundant families. Harvesting includes a wide variety of species and few individuals per species are harvested, but the use variesamong courses within the community; this use does not significantly affect the composition of species between FL and MV.Conclusions: Even though there are sections of the FL in which its vegetal cover is degraded, the strategies of current use allow the permanence andconservation of the composition of species at the local level. The intensity of exploitation in the FL is reflected by a greater number of roads and thedistance between them and the forest resources they use.